2018
DOI: 10.1038/s41467-018-06898-4
|View full text |Cite
|
Sign up to set email alerts
|

Mettl3-mediated m6A RNA methylation regulates the fate of bone marrow mesenchymal stem cells and osteoporosis

Abstract: N6-methyladenosine (m6A) is the most abundant epigenetic modification in eukaryotic mRNAs and is essential for multiple RNA processing events during mammalian development and disease control. Here we show that conditional knockout of the m6A methyltransferase Mettl3 in bone marrow mesenchymal stem cells (MSCs) induces pathological features of osteoporosis in mice. Mettl3 loss-of-function results in impaired bone formation, incompetent osteogenic differentiation potential and increased marrow adiposity. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
315
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(326 citation statements)
references
References 66 publications
10
315
0
1
Order By: Relevance
“…We also discovered that IGF1R expression decreased in the calluses of mouse fracture samples with injection of agomiR‐7025‐5p. Previous studies demonstrated that abnormal IGF1R expression plays an important role in the pathogenesis of acute lymphoblastic leukaemia, adrenocortical carcinoma, colorectal cancer and Ewing sarcoma . Thus, our findings indicate that the miR‐7025‐5p/IGF1R axis may play an important role in bone metabolism processes including osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…We also discovered that IGF1R expression decreased in the calluses of mouse fracture samples with injection of agomiR‐7025‐5p. Previous studies demonstrated that abnormal IGF1R expression plays an important role in the pathogenesis of acute lymphoblastic leukaemia, adrenocortical carcinoma, colorectal cancer and Ewing sarcoma . Thus, our findings indicate that the miR‐7025‐5p/IGF1R axis may play an important role in bone metabolism processes including osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…Suppressing adipogenesis by promoting cell cycle transition in mitotic clonal expansion [89] YTHDF2 Inhibiting autophagy and adipogenesis by decreasing protein expression of ATG5 and ATG7 and shortening the lifespan of their m 6 A-modified mRNAs [87] Suppressing adipogenesis by increasing m 6 A methylation of CCNA2 and CDK2 and reversing the methylation effect of FTO on CCNA2 and CDK2 [90,91] Inhibiting adipogenesis via the downregulation of CCND1 [92] NAFLD FTO Down-regulating mitochondrial content and up-regulating TG deposition [101] Promoting hepatic fat accumulation by increasing the expression of lipogenic genes, including FASN, SCD and MOGAT1, and intracellular TG level in HepG2 cells [101] Increasing oxidative stress and lipid deposition [99] YTHDF2 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] METTL3 Increasing lipid accumulation by decreasing both PPARα mRNA lifetime and expression [105] Hypertension m 6 A-SNPs EncodIing β1-adrenoreceptor, a hypertension-susceptibility candidate gene [108,109] Altering BP-related gene expression, mRNA stability and homeostasis [110] Cardiovascular diseases FTO Decreasing fibrosis and enhancing angiogenesis in mouse models of myocardial infarction [111] METTL3 Driving cardiomyocyte hypertrophy by catalyzing methylation of m 6 A on certain subsets of mRNAs [112] Decreasing eccentric cardiomyocyte remodeling and dysfunction [112] Inhibiting cellular autophagic flux and promoting apoptosis in hypoxia/reoxygenation-treated cardiomyocytes [113] Osteoporosis METTL3 Inhibiting adipogenesis and adipogenic differentiation via JAK1/STAT5/C/EBPβ pathway in bone marrow stem cells [119] Inhibiting osteoporosis pathological phenotypes, consisting of decreased bone mass and increased marrow adiposity via PTH/PTH1R signaling axis [118] FTO Promoting the differentiation of adipocyte and osteoblast by upregulating GDF11-FTO-PPARγ signalling way [116] Enhancing the stability of mRNA of proteins which function to protect osteoblasts from genotoxic damage through Hspa1a-NF-κB signaling way [120] Immune-related MDs ALKBH5 Expressing highly in organs enriched in immune cells with frequent immune reactions [10,123] METTL3 Stimulating T cell activation and the development of T lymphocytes in the thymus by regulating the translation of CD40, CD80 and TLR4 signaling adaptor TIRAP transcripts in den...…”
Section: Mettl14mentioning
confidence: 99%
“…The low bone mass and excessive accumulation of adipose tissue in bone marrow milieu can result in architectural deterioration of the skeleton, the decrease of bone strength and an increased risk of fragility fractures [114,115]. Recent released studies has suggested that m 6 A modification and its regulatory enzymes such as FTO, METTL3 are the key factors for osteoporosis [116][117][118]. The deletion of METTL3 in porcine bone marrow stem cells could promote adipogenesis and adipogenic differentiation via janus kinase 1 (JAK1)/signal transducer and activator of transcription 5 (STAT5)/CCAAT/ enhancer binding protein β (C/EBPβ) pathway [119].…”
Section: A Methylation and Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the determination of m 6 A content in mRNA or RNA by LC-MS/MS has been mentioned in some studies [2,[25][26][27][28]. However, the methods of quantifying m 6 A were only described briefly.…”
mentioning
confidence: 99%